Pengembangan Produksi UMKM Kudapan Kenari Dalam Meningkatkan Pendapatan Pengusaha Di Desa Mateketen Kecamatan Makian Barat Kabupaten Halmahera Selatan - Geovanny Valensyah M; Yetty; Musdar Muhammad; Firdaus Duko; Aswir Hadi (CV. ULIL ALBAB CORP, 2024)
This study aims to analyze the effect of raw materials, labor and investment (business capital) on the production of walnut snacks in Mateketen Village, West Makian District, South Halmahera Regency, along with the conditions of return to scale of walnut snack production in the study village. Also, analyze the effect of selling prices, sales volume and production costs on entrepreneurs' income, as well as the level of sensitivity (elasticity) of changes in the income of walnut snack MSME entrepreneurs in Mateketen Village to changes in selling prices, sales volume and production costs. Secondary data and primary data. Data analysis was carried out descriptively; geometric growth and econometric model analysis. using the double logarithm model or constant elasticity model. Based on the results of the double logarithm model regression analysis, simultaneously (collectively) the independent variables of raw materials, labor and investment have a significant effect on the production of walnut snacks in Mateketen Village, West Makian District, while individually, only the independent variables of raw materials and investment have a significant effect on the production of walnut snacks. Nevertheless, the production of walnut snacks in the village is in a condition of increasing returns to scale. Furthermore, based on the results of constant elasticity analysis, collectively and individually, the independent variables of selling price, sales volume and production cost have a significant effect on the production of walnut snacks.